C-reactive protein: a marker of neonatal stress?. (April 2014) - Bellieni, C. V.; Liuzzo, L. P.; Giomi, S.; Tei, M.; Stazzoni, G.; Bertrando, S.; Cornacchione, S.; Braconi, F.; Zurli, L.; Buonocore, G.
Abstract Aim: To assess whether blood values of C-reactive protein (CRP) in healthy term newborns, are influenced by stress. Material and methods: Since different types of delivery (vaginal delivery [VD], emergency C-section [EMCS] and elective C-section [ELCS]) are notoriously characterized by different levels of stress for the baby, these three groups were used as models of different levels of stress. The mean CRP values of the three groups obtained in the first hours of life were compared. Results: We retrieved 1012 babies. Median values (3rd–97th ct) were: 0.05 (0.01–0.46), 0.17 (0.02–1.54), 0.30 (0.04–1.77), 0.43 (0.05–1.31), 0.40 (0.04–1.13) at 12, 24, 48, 72 and 96 h, respectively. Mean values in babies born after VD were statistically higher than those born after C-section, and higher CRP values were present in EMCS with respect to ELCS. Conclusion: This study described normal blood CRP values in a wide population of term babies. An influence of the type of delivery on blood CRP is evident, and this may be explained by the different amount of perinatal stress induced by anyone of the three types of delivery we considered.